2014
DOI: 10.1097/dss.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Brief Educational Video Administered by a Portable Video Device to Improve Skin Cancer Knowledge in the Outpatient Transplant Population

Abstract: These findings suggest an inherent appeal for audio-visual presentation and point its potential to improve patients' knowledge of their increased risk of skin cancer and preventive skin cancer measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
(22 reference statements)
1
13
1
Order By: Relevance
“…Conflicting data exist with regard to the efficacy of sun protection education in OTRs. While our data suggest that patients prefer to receive information verbally and through educational pamphlets, Trinh et al showed that video education is more effective than pamphlets at increasing patient knowledge. In contrast, a study by Loescher et al found both educational videos and informational brochures to be effective.…”
Section: Discussioncontrasting
confidence: 89%
“…Conflicting data exist with regard to the efficacy of sun protection education in OTRs. While our data suggest that patients prefer to receive information verbally and through educational pamphlets, Trinh et al showed that video education is more effective than pamphlets at increasing patient knowledge. In contrast, a study by Loescher et al found both educational videos and informational brochures to be effective.…”
Section: Discussioncontrasting
confidence: 89%
“…Significant knowledge gains were observed among the participants from the pretest to posttest ( P < 0.05; data not shown). This is consistent with numerous studies conducted in the health industry where videos were used to improve the viewer's knowledge on a health‐related subject (Brace and others ; Del Carmen Cabesa and others ; Trinh and others ). The entirety of knowledge gains cannot be attributed to the videos, but the videos likely contributed to knowledge gains to some extent.…”
Section: Evaluation Phasesupporting
confidence: 89%
“…Adoption of these educational initiatives can be simplified by the current ubiquity of electronic resources and audiovisual communication. Indeed, this has been the inspiration behind turning to video education as an effective modality for the presentation of concise, easily understandable patient information to fill the gap between currently delivered and understood health information ( Trinh et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%